What is new in perinatal HIV prevention?. Issue 1 (February 2018) - Fowler, Mary G.; Flynn, Patricia; Aizire, Jim
Abstract : Purpose of review: The purpose of this review is to describe recent clinical trial, laboratory and observational findings that highlight both the progress that can be achieved in elimination of new pediatric infections in international clinical trial settings among HIV-infected breastfeeding women while also describing recent safety concerns related to currently used antiretroviral regimens. The article will also address the ongoing adherence challenges for HIV-infected mothers in taking their antiretroviral drugs. This information is timely and relevant as new regimens are being considered for both prevention of mother-to-child transmission (PMTCT) of HIV and HIV treatment options worldwide. Recent findings: The main themes described in this article include both efficacy of different antiretroviral therapy (ART) regimens currently being rolled out internationally for PMTCT as well as safety findings from recent research including a large multisite international trial, PROMISE. Summary: The findings from the IMPAACT PROMISE trial as well as other recent trial and observational findings suggest that while progress has been steady in reducing PMTCT worldwide, the goal of virtual elimination of pediatric HIV worldwide will require careful attention to optimizing safety of new regimens which are less dependent on maternal daily ART adherence and safer in preventing certain toxicities.